The fossil record of South American short-faced bears (Ursidae, Tremarctinae) - Bond, Mariano (2005)
The present study includes a review of the geographic and stratigraphic distribution of short-faced bears (Ursidae, Tremarctinae) in South America. In addition, the authors discuss biogeographic hypotheses regarding the origin of South American tremarctines. The Tremarctinae subfamily is distributed exclusively in America, from Alaska to southern Patagonia. Its biochron comprises the temporal lapse between Late Miocene and recent times; the first record of Tremarctinae in North America corresponds to the Hemphillian and the last to the Rancholabrean. In South America, the first record corresponds to the Ensenadan. In the present day, it corresponds to the only living tremarctine, the "Andean Bear," but short-faced bears became extinct during the early Holocene. The extinction of short-faced bears in North and South America appears to have been approximately synchronous. Finally, the fossil record in South America indicates species turnover between the Ensenadan and Bonaerian, during which time the giant species Arctotherium angustidens was replaced by Arctotherium tarijense, Arctotherium bonaeriense, and Arctotherium vetustum (and probably Arctotherium wingei).